2001
DOI: 10.1002/ffj.965
|View full text |Cite
|
Sign up to set email alerts
|

Localities and seasonal variations in the chemical composition of essential oils of Satureja montana L. and S. cuneifolia Ten

Abstract: The essential oils of Satureja montana L. and Satureja cuneifolia Ten. were subjected to detailed GC-MS analysis in order to determine possible similarities between them and also the differences in their chemical compositions, depending on the locality and the stage of development. The plant materials were collected prior to, during and after flowering from three different locations in the central part of Dalmatia (Croatia). For both plants the qualitative composition of the components appeared to be constant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
6
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 8 publications
6
64
6
1
Order By: Relevance
“…Analyses of glycosidically bound volatiles and antioxidant activity of free volatile compounds were previously reported for S. montana L. [9] [10]. Monoterpenes are usually present as main constituents of the aglycones as well as the main components in essential oil composition of aerial parts of Satureja plants [5] [11] [12]. In the literature data, we found no other published results dealing with the glycosidically bound volatiles of other Satureja species.…”
Section: Introductioncontrasting
confidence: 49%
“…Analyses of glycosidically bound volatiles and antioxidant activity of free volatile compounds were previously reported for S. montana L. [9] [10]. Monoterpenes are usually present as main constituents of the aglycones as well as the main components in essential oil composition of aerial parts of Satureja plants [5] [11] [12]. In the literature data, we found no other published results dealing with the glycosidically bound volatiles of other Satureja species.…”
Section: Introductioncontrasting
confidence: 49%
“…Beside this, it was found that the specimens collected during the flowering season had the highest content of the carvacrol and thymol and their precursors p-cymene and γ-terpinene [7,15,17]. Finally, differences in the chemical compositions not only reflects the genetic variability of the genus Satureja [19], but also the variability within the same species, as in the case of the S. hortensis [28].…”
Section: Discussionmentioning
confidence: 99%
“…According to the avaliable literature, there are chemical differences of this plants' essential oils, obtained from specimens collected at different localities [4,[14][15][16] and in different ontogenetic stages [7,15,17]. It is important to note that in the mentioned investigations, their antimicrobial activities were either not tested or the authors didn't investigated the relation between chemical composition and the obtained activity of the essential oil [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations proved the strong phenolic character of essential oils from oregano (Origanum vulgare L.) (Lagouri et al, 1993;Milos et al, 2000;Vichi et al, 2001), thyme (Thymus vulgaris L.) (Schwarz and Ernst, 1996), wild thyme (Thymus serpyllum L.) (Mailhebiau, 1994) and savory (Satureja montana L.) (Radonic and Milos, 2003). On the other hand, the Satureja cuneifolia essential oil (of Croatian origin) was found to contain a low percentage of phenolic compounds (Milos et al, 2001).…”
Section: Introductionmentioning
confidence: 99%